Contributions to the conservation of Plecoptera (Insecta) in Argentine Patagonia: taxonomy and distribution in the context of climate change - Duarte Simoes, Tacio Vitor (2024)
The conservation of Plecoptera (stoneflies) in Argentine Patagonia is a critical endeavor, especially in the context of climate change. The limited understanding of Patagonian Plecoptera fauna, with many species’ records confined to their original descriptions and isolated citations, poses a significant challenge for studies in distribution, ecology, and biogeography. To address these gaps, our ongoing project aims to improve the knowledge of Patagonian Plecoptera through taxonomic research coupled to distributional studies. The taxonomic research involves using both morphological and molecular data to better define species boundaries, aiding in associating different life stages and sexes with their respective species. This approach has been particularly beneficial in reviewing the genus Notoperla Enderlein. Additionally, we aim to generate predictive distribution models against different climate change scenarios, drawing from a massive database developed through 15 years of extensive sampling across Argentine Patagonia. Our collaboration has also enabled us to integrate diverse sources of information, merging niche modeling and distribution analysis, representing an unprecedented study for the insects of Patagonia. Our partnership with researchers from Universidade Estadual Paulista (UNESP), Brazil, has facilitated the acquisition of molecular data, enhancing our understanding of Plecoptera biodiversity. Upon the conclusion of this project, we hope to achieve the following results: updated diversity, genetic library, and distributional patterns of South American Plecoptera; identification of taxonomic novelties within Gripopterygidae; and integrative/iterative taxonomy and distributional information of Notoperla. Future research prospects involve distributional analyses of Neotropical and Patagonian Gripopterygidae. The understanding and conservation of Plecoptera in Argentine Patagonia are crucial not only for preserving the biodiversity of the region but also for gaining insights into the impacts of climate change on this taxon. This initiative aims to offer crucial information for conserving Plecoptera in the face of climatic changes.